Inklusi Disabilitas Dalam Layanan Kesehatan: Survey Aksesibilitas, Jejaring Dan Kolaborasi - Kristinawati Kristinawati; Eka Ratnawati; Ranie Ayu Hapsari (STIKES Ngesti Waluyo, 2026)
People with disabilities are a vulnerable group who often experience barriers in accessing health care facilities, including health care products. Health care facilities have an important responsibility to meet inclusive service accessibility standards, ensuring that health care is accessible to all parties, including people with disabilities. This article provides an overview of healthcare facilities’ readiness to provide inclusive access to health care. Using a survey method, 91 health care institutions or facilities completed a questionnaire on the accessibility of inclusive services. The survey results indicate that most health care facilities have a strong commitment and support for implementing and developing inclusive services. However, in practice, some health care facilities face limitations related to resource capacity and capabilities, infrastructure, networking, and collaboration. The challenges in ensuring health care accessibility require each health care facility to assess the need for support in implementing accessibility standards, networking, and collaboration